Clinical features and outcomes of adult patients with single ventricle physiology not undergoing Fontan repair. (25th November 2020) - Gordon, B; Buendia Fuentes, F; Dos, L; Miranda, B; Osa, A; Gonzalez, A; Gallego, P; Meras, P; Adsuar, A; Rodriguez, M.J; Montserrat, S; Carbonell, B; et al.
Abstract: Background: Adult patients with single ventricle (SV) physiology who had not undergone Fontan palliation are uncommon. Little is known about their clinical features and outcomes. Objective: This study aims to describe the clinical features, cardiovascular outcomes and long-term survival of patients with SV physiology without Fontan palliation. Methods: Data were collected retrospectively from SV physiology patients followed in adult congenital heart disease (ACHD) units of five tertiary referral centers. None of them had Fontan palliation. Baseline data were recorded on the first visit at ACHD unit. Death was considered as main endpoint. Other outcomes such as atrial or ventricular arrhythmias, endocarditis, ICD or pacemaker implantation, admission for heart failure and heart transplant were also collected and analyzed. Association between clinical/analytical baseline variables and death was also evaluated by univariate Cox regression. Results: 128 patients were included. On the first visit, mean age was 32.3±10.9 years, being the most common defect double inlet left ventricle (63p, 49.2%). The single ventricle had left morphology in 106 cases (82.8%). At baseline mean heaemglobin was 19.1±2.8 g/dl, mean O2 Sat 83±6.9% and 46 patients (36%) had a NYHA status III or IV. 4 different groups were found: a) Unrestricted pulmonary flow with Eisenmenger physiology (24p, 18.8%); b) Restricted forward pulmonary flow with or without pulmonary banding (46p, 35.9%); c) Aortopulmonary shunts as a source of pulmonary flow (20p, 15.5%) and d) cavopulmonary shunt (Glenn) as a definitive palliation (38p, 29.7%). After 7.3±4.1 years follow-up, mortality was 22.7% (29 patients), being sudden death (9p, 7%) the most frequent cause. Survival rate at 5 and 10 years of follow-up were 85% and 76% respectively (Figure 1). About of the rest of the outcomes, highlighting a high rate of atrial tachycardia (38.3%), admission for heart failure (23.4%), stroke (17.2%), endocarditis (9.4%), pacemaker/ICD implantation (11.8%). Baseline variables associated with higher mortality were: older age (HR=1.1 [1.004–1–087]); NYHA III or IV (HR=5.5 [2.4–12.4]); thrombocytopenia (HR=1.01 [1.001–1.003]); anticoagulant treatment (HR=2.6 [1.7–3.9]); glomerular filtration rate below 60 ml/min (HR=3.77 [1.5–9.6]); QRS width (HR=1.03 [1.01–1.05]); atrial arrhythmias (HR=3.1 [1.5–6.5]); moderate or severe AV valve regurgitation (HR=1.5 [1.15–1.97]) and ventricular ejection fraction (HR=0.94 [0.91-0.97]). Conclusions: Adults survivors with SV physiology without Fontan palliation have a high mortality and frequently suffer from serious cardiovascular events. Several clinical (NYHA status, previous atrial arrhythmias, anticoagulant treatment), analytical (renal function, thrombocytopenia), ECG (QRS width) and echocardiography (AV valve regurgitation and EF) factors can identify patients at higher risk of death. Funding Acknowledgement: Type of funding source: None